Organizational Structure Change and Hybridity: Enhancing Uncertainty as a Response to Competing and Changing Institutional Logics - Liu, Liming; Zhang, Chao (Frontiers in Psychology, 2022)
Confronting the uncertain environment, this article adopts a case research approach to resonate with the studies of hybridity. It aims to explain how the perception of uncertainty in the institutional environment affects the adaptation of organizational structure in pursuing legitimacy for hybrid organizations. Based on the empirical data collected from a two-staged fieldwork and in-depth interviews, the case analysis concentrates on the correlation between the evolution of institutional logics and organizational structure change from a diachronic perspective. The findings indicate that in the face of competing and changing institutional logics, Chinese mass media organizations have gradually shifted from a dominated blending strategy in the exploration stage to a deeply compartmentalizing strategy in the stable stage. The hybrids can deal with the uncertainty of the institutional environment by enhancing the uncertainty of the organizational structure. Consequently, the case evolves an organizational integration through internal legitimacy. It manifests a possibility for hybrids of combining the two major response mechanisms in one process.